2018
DOI: 10.1115/1.4038847
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Performance of Drag-Reducing Polymers in Single- and Multiphase Horizontal Flow Using Particle Image Velocimetry

Abstract: This paper presents experimental investigations conducted to understand the influence of water-soluble drag-reducing polymers (DRPs) in single- and two-phase (stratified wavy) flow on flow-field characteristics. These experiments have been presented for water and air–water flowing in a horizontal polyvinyl chloride 22.5-mm ID, 8.33-m long pipe. The effects of liquid flow rates and DRP concentrations on streamlines and the instantaneous velocity were investigated by using particle image velocimetry (PIV) techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The subsequent journal publications mostly report about the hydrodynamic theories of drag reduction (DR) and the effects of DRP MW and stability, rheology, multiphase flow, hydrodynamic variables, conduit configuration, surfactant-based product formulation, etc. on the performance of commercial DRPs [14][15][16][17][18][19][20][21][22][23]. These references and the citations therein can be pursued for the details.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent journal publications mostly report about the hydrodynamic theories of drag reduction (DR) and the effects of DRP MW and stability, rheology, multiphase flow, hydrodynamic variables, conduit configuration, surfactant-based product formulation, etc. on the performance of commercial DRPs [14][15][16][17][18][19][20][21][22][23]. These references and the citations therein can be pursued for the details.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to express the reduction in the energy consumption is the drag reduction percentage (%DR) along the pipeline. This parameter that has been extensively used in many research works dealing with the topic of drag reducing polymers (DRPs) 8 , 11 , 17 . This index can be defined in the context of this work as relative pressure difference (or head difference) between non-treated (subscript N) and treated pipes (subscript T).…”
Section: Methodsmentioning
confidence: 99%
“…Drag reduction (DR) is defined as the ability to reduce the frictional resistance in turbulent flows in the pipeline, particularly using low concentrations of certain additives. These additives can be classified as follows: polymers, surfactants, fibers, micro-bubbles, and compliant coating 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Sarkhi et al [20,21,22] summarized from their experimental results that higher drag reduction usually occurs in the transition from slug or annular flow to stratified flow using the polymer drag-reducing agents. More recent studies can be found in references [23,24,25]. All these authors described many important factors on the drag reduction rate of gas-liquid turbulent flow.…”
Section: Introductionmentioning
confidence: 99%